2005
DOI: 10.1103/physrevb.72.035208
|View full text |Cite
|
Sign up to set email alerts
|

Structure and vibrational properties ofNH2complexes in GaAs:N

Abstract: Considerable attention has been focused on GaAs:N since it was discovered that the addition of nitrogen to gallium arsenide leads to a surprisingly large reduction in its band gap and changes in its electronic properties. Equally surprising was the discovery that subsequent hydrogenation largely negates these effects, generating a material whose properties are similar to those of GaAs. Infrared studies of the hydrogenated defect indicate that it contains two hydrogen atoms. Despite the efforts that have been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The absence of the 2217 cm -1 band in some samples where the three other bands related to one specific N-D complex are present [14], challenges the model of the H-N-H center proposed recently [11,12]. The sites of the two H atoms in this model, say H A and H B , are inequivalent due to a slight rotation of the H A -N-H B complex around the vertical [110] direction, causing two different H-Ga stretching frequencies.…”
Section: Results and Discussion After Treatment With Hmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of the 2217 cm -1 band in some samples where the three other bands related to one specific N-D complex are present [14], challenges the model of the H-N-H center proposed recently [11,12]. The sites of the two H atoms in this model, say H A and H B , are inequivalent due to a slight rotation of the H A -N-H B complex around the vertical [110] direction, causing two different H-Ga stretching frequencies.…”
Section: Results and Discussion After Treatment With Hmentioning
confidence: 99%
“…The calculations of Fowler et al [11] and Du et al [12] showed that a canted H-N-H complex could provide an explanation for two high-frequency but slightly different stretching modes of H(D), as experimentally observed. The symmetry of this complex is C 1h , but the deviation from the symmetrical C 2v configuration, as first discussed by Amore Bonapasta et al [19], is only small.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…1) eliminates the band gap shift caused by N and explains the experimentally observed vibrational properties of the deuterated alloy. [10][11][12][13] (The deuterated D-N-D defect is more easily studied by vibrational spectroscopy than the corresponding H-N-H center and is the focus of this paper.) The results of x-ray absorption near-edge spectroscopy (XANES) experiments and their interpretation have also been found to be consistent with a D-N-D complex.…”
mentioning
confidence: 99%
“…These materials show a very strong band gap bowing with increasing nitrogen concentration [2,3]. Post-growth annealing of these dilute nitrides induces a noticeable blue-shift of the band-gap [1], while post-growth hydrogenation effectively passivates the incorporated nitrogen atoms due to the formation of various N-H complexes [4,5].…”
mentioning
confidence: 99%